Cellular communication network factor 1‐stimulated liver macrophage efferocytosis drives hepatic stellate cell activation and liver fibrosis. Issue 10 (5th August 2022) - Kim, Ki‐Hyun; Cheng, Naiyuan; Lau, Lester F.
Abstract: Following inflammatory injury in the liver, neutrophils quickly infiltrate the injured tissue to defend against microbes and initiate the repair process; these neutrophils are short lived and rapidly undergo apoptosis. Hepatic stellate cells (HSCs) are the principal precursor cells that transdifferentiate into myofibroblast‐like cells, which produce a large amount of extracellular matrix that promotes repair but can also lead to fibrosis if the injury becomes chronic. The matricellular protein cellular communication network factor 1 (CCN1) acts as a bridging molecule by binding phosphatidylserine in apoptotic cells and integrin αv β3 in phagocytes, thereby triggering efferocytosis or phagocytic clearance of the apoptotic cells. Here, we show that CCN1 induces liver macrophage efferocytosis of apoptotic neutrophils in carbon tetrachloride (CCl4 )‐induced liver injury, leading to the production of activated transforming growth factor (TGF)‐β1, which in turn induces HSC transdifferentiation into myofibroblast‐like cells that promote fibrosis development. Consequently, knock‐in mice expressing a single amino acid substitution in CCN1 rendering it unable to bind αv β3 or induce efferocytosis are impaired in neutrophil clearance, production of activated TGF‐β1, and HSC transdifferentiation, resulting in greatly diminished liver fibrosis following exposure to CCl4 . Conclusion: These results reveal the crucial role of CCN1 in stimulating liver macrophage clearance of apoptotic neutrophils, a process that drives HSC transdifferentiation into myofibroblastic cells and underlies fibrogenesis in chronic liver injury. Abstract : We show that CCN1 induces liver macrophage efferocytosis of apoptotic neutrophils in CCl4 ‐induced liver injury, leading to the production of activated TGF‐β1, which in turn induces HSC transdifferentiation into myofibroblast‐like cells that promote fibrosis development. These results reveal the crucial role of CCN1 in stimulating liver macrophage clearance of apoptotic neutrophils, a process that drives HSC transdifferentiation into myofibroblastic cells and underlies fibrogenesis in chronic liver injury.image